Economic impact of government expenditure : an analysis in input-output framework / Atul Sharma, V.B. Tulasidhar - Sarma, Atul. (New Delhi, 1984)
The share of government expenditure in the national economy has grown phenomenally the world over. Very much in tune with this universal trend, in India it rose from a little over nine per cent of GNP in the early fifties to about twenty four per cent by the late seventies. Government intervention in economic management in terms of massive public investment and expenditure programmes under successive Plans is largely responsible for this growth. Comprehension of the overall sectoral demand implications of such investment and expenditure programmes is necessary to achieve the physical balances in the economy. It is in this context that the study of the impact of government expenditure becomes important. A few studies have attempted to estimate but in a partial manner the sectoral demand implications of the Central Government expenditure confining themselves to commodity purchases and ignoring the most important salary component. The present study makes a first ever attempt in the Indian context to develop a suitable methodology to make the salary component amenable to analysis in the input output framework apart from estimating the sectoral requirements of commodity purchases of the Union Government. In addition, it studies the sensitivity of different sectors to changes in the level of government expenditure, and the import and employment requirements. Carrying out two exercises one in consistency and the other in Linear programming framework-it also studies the compatibility of the government induced demand with the excess capacities known to exist in most manufacturing sectors. Economists, administrators, planners and policy makers should find this book of immense interest and utility.
Keywords: "Expenditure, public"